A New Stage in Russia-Japan Relations: Rapprochement and its Limitations. (3rd July 2019) - Kireeva, Anna
Abstract : Since May 2016 Russia-Japan relations have entered a new stage characterized by the unprecedented activity aimed at improving relations in a comprehensive way: political and security dialogue, confidence building measures, new economic projects and people-to-people contacts. However, apart from the old problems, new limitations and asymmetries have emerged that hinder the development of bilateral relations against the background of power shift and changing strategic environment in East Asia. The article seeks to assess how deep is Russia-Japan rapprochement, what are the motivations of the two countries, major limitations, both domestic and external, expectation asymmetries and misperception gaps. It discusses the developments after the agreement between Russia's President Vladimir Putin and Japan's Prime Minister Shinzo Abe in November 2018 to facilitate negotiations on a peace treaty and territorial issue based on the Soviet-Japanese Declaration of 1956, and how tangible is a breakthrough. The article concludes by providing an argument for forging stronger Russia-Japan partnership and discusses the potential of bilateral relationship.